Simultaneous pancreas--kidney transplantation: to anticoagulate or not? Is that a question? - Vaidya, A; Muthusamy, A; Hadjianastassiou, V; Roy, D; Elker, D; Moustafellos, P; Muktadir, A; Sinha, S; Friend, P (2007)
Pancreas graft loss due to venous thrombosis is the leading non-immunological cause for graft failure following kidney-pancreas transplantation. Thromboelastography (TEG)-directed anticoagulation protocol has shown that approximately one-third of the patients undergoing pancreas transplantation require therapeutic anticoagulation to prevent the occurrence of graft thrombosis. This article presents the argument for individualised anticoagulation in these patients based on their TEG tracings and suggests the use of TEG in patients undergoing pancreas transplantation.